Effect of Isosporiasis Prevention with Toltrazuril on Long-Term Pig Performance - K. Rypula; M. Porowski; J. Kaba; M. Gorczykowski; A. Deniz (The Scientific World Journal)
The efficacy of toltrazuril treatment was assessed in two experiments in Polish swine herds. Experiment 1 included a toltrazuril treatment group, Group A (n=410), and untreated control, Group B (n=386). Time to sale in Group A was 108 days versus 120 days for Group B, with average body weights at sale of 114.2 kg and 108.8 kg, respectively (P<0.05). In experiment 2, the health status and body weight gain of 238 piglets treated with toltrazuril (Group D) were compared to 235 untreated piglets (Group K). A similar difference was observed in average body weights of slaughtered animals, being on average 104 kg in Group D and 101 kg in Group K (P<0.01). Animals from Group D were slaughtered 5 days earlier than animals from Group K (day 166 versus day 171). Data from clinical trials suggest treatment of coccidiosis with toltrazuril offering potential for improved animal welfare and yields, however this has remained unproven in field conditions in large swine production facilities. The present study confirms the efficacy of toltrazuril treatment when used in the field and the subsequent positive impact on time to weaning, time to market, and on weight gain at all time points.